Reformasi Hukum Di Bidang Informasi Dan Transaksi Elektronik - Tarigan, Sion; Maria Trianggraini, Anna (Jurnal Syntax Fusion, 2023)
Legal reform or renewal is an attempt to replace the existing legal rules in society in accordance with social, political developments and aspirations regarding the legal order aspired to by the community, one of which is renewal in the field of Information and Electronic Transactions, namely the ITE Law Number 11 of 2008 which an amendment has been made, namely Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions, where the changes are intended to anticipate problems regarding ITE, and make it easier for law enforcement officials to take action against perpetrators, this research uses normative legal research on written regulations, so this research refers to literature because it requires data from literature, and in this legal research the data used, namely secondary data on the implementation of the ITE Law from 2008 to 2016, has many problems, such as provisions prohibiting the spread of illegal content often intersect with the protection of freedom of expression as a right protected and guaranteed by the constitution, more The ITE Law also presents a space for uncertainty in law enforcement, several criminal provisions in the ITE Law are duplicative and give the impression of overlapping with the provisions in the Criminal Code (KUHP), and are broadly formulated but have multiple interpretations. unclear, and contrary to the principle that criminal law must be clear or commonly called (lex certa) and strictly formulated (lex stricta). Reforms in the field of Information and Electronic Transactions have not shown significant changes and impacts on society, because they do not touch on the main issues in the 2008 ITE Law, issues related to the provisions and implementation of the ITE Law are still far from ideal, therefore it can be concluded that the possibility of updating the ITE Law Number 19 of 2016 is very wide open.